The way to Bea - Yeh, Kat (Little, Brown and Company, 2018)
Recently estranged from her best friend and weeks away from shifting from only child to big sister, seventh grader Beatrix Lee consoles herself by writing haiku in invisible ink and hiding the poems, but one day she finds a reply--is it the librarian with all the answers, the editor of the school paper who admits to admiring her poetry, an old friend feeling remorse, or the boy obsessed with visiting the local labyrinth?